Two Cases of Sarcoma Arising in Giant Cell Tumor of Bone Treated with Denosumab - Cory Julian Broehm; Erika L. Garbrecht; Jeff Wood; Therese Bocklage (Case Reports in Medicine)
Giant cell tumor (GCT) of bone is a generally benign, but often locally aggressive, neoplasm of bone, with a propensity for recurrence. Sarcomatous transformation is rare and typically occurs with a history of recurrences and radiation treatment. Denosumab, an inhibitor of the RANK ligand involved in bone resorption in GCT, is increasingly used in treatment of recurrent or unresectable giant cell tumor of bone. We report two cases of sarcomatous transformation of GCT to osteosarcoma in patients receiving denosumab. One was a 59-year-old male with a 12-year history of GCT and multiple recurrences taking denosumab for 2.5 years. The second case was in a 56-year-old male with a seven-year history of GCT taking denosumab for six months. Review of the literature shows one case report of malignant transformation of GCT in a patient being treated with denosumab. As the use of denosumab for treatment of GCT will likely increase, larger, controlled studies are needed to ascertain whether denosumab may play a role in malignant transformation of giant cell tumor of bone.